Pope's Chapel United Methodist Church Forty-second Annual Homecoming, October 4, 1998 - (:unkn) unknown (Wilkes County, Georgia: Pope's Chapel First Methodist Church)
Pope's Chapel United Methodist Church Forty-second Annual Homecoming, October 4, 1998. Jerry Kane, pastor. Event program. 2 copies, 1 with handwritten notes. Pope's Chapel First Methodist Church. Wilkes County, Georgia. United States.
1 electronic document. popes-chapel_program_19981004.pdf. 7 pages. 44149196 bytes (master).
Keywords: Church history; Congregational churches; Homecoming; Methodist Church--Anniversaries, etc.; Methodists; Pope's Chapel United Methodist Church (Wilkes County, Ga.); Programs (Publications); United Methodist Church (U.S.); Wilkes County (Ga.); Georgia; Asbury, Francis; Bamford, Sophia; Bamford, Sophia Boyd; Bohler, Clarence; Bohler, Genie R.; Boyd, Christine; Boyd, Deane; Boyd, Emory; Boyd, Fortson; Boyd, James Emory; Boyd, John Wright; Bunch, Greg; Bunch, Linda; Butler, Gene; Butler, Gwen; Butler, Jewell; Butler, Robert; Cash, M.T.; Chafin, David; Chafin, Elizabeth; Chafin, Malcolm; Combs, Hazel; Fortson, Benjamin Winn; Harris, Lundye; Humphries, Thomas; Kane, Jerry; Landrum, John; Neal, Augustus A.; Norman, Jimmy; Ogilvie, Hannah Rebecca; Pope, Henry; Roland, Edward; Sale, David; Smith, George; Wheatley, Elaine; Wiggins, Tom